Мелогеографічні особливості структури танцювально-приспівкових форм у традиції українців - Хай, М. (Студії мистецтвознавчі, 2007)
Music tunes of the folklore instrumental performance in Carpathian region despite of their basic affinity are very variable (due to historical and political causes). In Ukrainian music scholarship the questions of the structural typology did not attract enough attention. The genre specifics of the presented here cultural layers of the traditional Ukrainian music proves its both national and regional individuality and the ability to be mobile (within the genres, regions, cultures).